(untitled) (Research, Society and Development, 2022)
Objective: To investigate the existence of scientific evidence in the literature linking pregnant women with SARS-CoV-2 to preterm labor. Method: This is an integrtaive review carried out in the following databases: BVS, SciELO, MEDLINE/PubMed e Cochrane. Eighteen studies were included. Results: The most common comorbidities were hypertension and diabetes. There were mentions of intrauterine growth restriction and low birth weight newborns. The most common type of delivery was cesarean and the occurrence of premature births was described in all studies. In 77,7% of the studies, neonates tested positive for COVID-19. Conclusion: Worsening maternal status may indicate a risk factor for premature birth. Neonatal infection by SARS-CoV-2 has been reported, but there are gaps in the mechanism of vertical transmission and the impacts for preterm infants. The prematurity rate in pregntant women infected with COVID-19 is higher than in healthy pregnant women.